THE STUDY USE BETEL LEAVES EXTRACT ( Piper betle ) WITH DIFFERENT CONCENTRATION OF BREAKING STRENGTH AND ELENGATION TETORON YARN - Khairunnisa Amini; Isnaniah '; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on March 2015, which is held in the Laboratory of fishing Gear Materials, Utilization of Water Resource, The Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this research was to determine the effect of the use of preservatives fiber betel leaf extract (Piper betle) with different concentrations of the breaking strength and elengation PES yarn (Polyester). So it can determine the best concentration of the extract. From the measurement of breaking strength tetoron thread that has been getting treatment, the thread tetoron with treatment B (0.7 Kg / Liter of water) has the highest average 5.3 kgf, and followed by treatment of A (0.5 Kg / Liter water), and treatment C (0.9 Kg / Liter of water) with each value of the breaking strength of 5.15 kgf and 5.05 kgf. Tetoron yarn elengation which have been getting treatment, the thread tetoron with treatment B (0.7 Kg / Liter of water) has the highest average is 33.5 mm, and is followed by treatment of A (0.5 Kg / Liter of water) and treatment C (0.9 Kg / Liter of water) with each tetoron yarn elengation are 531.9 mm and 30.2 mm.Keywords : Breaking Strength , Elengation , Tetoron Yarn , Betel Leaves